More does not mean better: Frequency and accuracy analysis of lexical bundles in Chinese EFL learners' essay writing. (October 2015) - Huang, Kaisheng
Abstract: Previous research on lexical bundles, the most frequently occurring multi-word sequences in a given register, has mostly focused on frequency and classification analysis and has not fully addressed the question of how accurately these bundles are used by English as second (ESL) or foreign language (EFL) learners. This study aims to describe and compare both the frequency and accuracy of lexical bundles used by junior year and senior year English major students in Chinese universities. The results indicate that though senior students tend to produce lexical bundles more frequently and with a wider variety in their essay writings, they have not used lexical bundles significantly more accurately than their junior counterparts. It can be concluded that Chinese EFL learners have only achieved quantitative gain but failed to make significant progress in quality bundle use during their four years of English learning. Common misuses are documented and categorized for more explicit and effective instruction to further strengthen L2 learners' phraseological competence.